REVITALISASI PENGELOLAAN ECENG GONDOK DALAM UPAYA MENINGKATKAN EKONOMI MASYARAKAT DI DESA SEGARAN - Fista Apriani Sujaya; Ratna Wulan (Publika Citra Media, 2026)
The problem of water hyacinth (Eichhornia crassipes) in Segaran Village not only affects the environment but also hampers the community’s economic potential, as it has long been regarded merely as a weed. This community service program aimed to revitalize the utilization of water hyacinth through a structured and sustainable approach. The activities focused on empowering housewives through socialization, technical training, business mentoring, and evaluation. The method was designed to ensure that the community gained not only temporary knowledge but also skills that could be continuously developed independently. The results showed an increase in the capacity of housewives to process water hyacinth into various handicraft products with market value. In addition, the community began to recognize the importance of business management through simple financial recording, production management, and marketing strategies. Although the economic impact is still limited to the local scope, this program has opened opportunities for household economic independence and reduced dependence on informal loans. Thus, the program contributes not only to increasing income but also to environmental management, while serving as a foundation for the development of community-based economic activities utilizing local resources.